UJI ANTAGONISME BEBERAPA Trichoderma sp TERHADAP PENYAKIT BUSUK PANGKAL BATANG (Ganoderma boninense) PADA MEDIA PADAT DI LABORATORIUM - Mariani Sembiring; Muhammad Yusuf Dibisono; Hendrik Dharmansyah (Institut Teknologi Sawit Indonesia, 2017)
Ganoderma boninense is afungus that causes the disease rotting the roots (basal stem rot). Infection and disease transmission generally occurs through the contact ofthe root or the base ofthe stem with a source inokulum in the ground. Ganoderma boninense can cause death in plant oil palm. Trichoderma sp saprofik is a fungus that lives in the soil, litter, dead wood, and living in various places. Easy to find, quickly, and which were capable o f killing other fungi. Based on this research done antagonism Trichoderma sp Ganoderma boninense against media PDAS.This research was carried out in the laboratory ofSoil Biology Faculty ofAgriculture University ofNorth Sumatra. This research was carried out on 15 June-6 July 2016. This study used a Randomized Complete Design method (RAL) non Factorial treatment 2 and 11 replicates. Testing conducted the smallest Real Difference test (BNT) and the 5% level. The research results showed that T4 Treatment (g. boninense + 1. harzianum) produces the best drag power against pathogen growth o f g. boninense with percentage o f barriers of 344.53% showed that treatment oft. harzianum was able to inhibit the growth ofg. boninense process occurs through inhibition ofantagonistic mechanism ofthe inhibitory zones are characterized by thepresence.